MABBACA DOANG DI PASAKA BONE - Andi Siska Putri Utami Arifin; Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2019)
study aims to find out 1) why the people of Kaka District, Pasaka Village, Bone Regency do Mabbaca Doang. 2) the meaning of Mabbaca Doang to the people in Pasaka Village, Kahu District, Bone Regency. And the function of Mabbaca Doang in Pasaka Village, Kahu District, Bone Regency. This type of research uses qualitative research with descriptive analysis. Data collection techniques are carried out using the method of observation, interviews, and documentation by involving individuals as many as five informants. Based on the results of the study show that: 1. The local community carried out the tradition of mabbaca doang in Pasaka Village, Kahu District, Bone Regency, because mabbaca doang was considered a proper heritage to be maintained because the process was not so burdensome and its intention was due to Allah and if it was not done , they believe that something will happen to their lives. 2. The meaning of mabbaca doang for the people of Pasaka Village is first as a form of gratitude to God and the second as repellent. 3. The function of the mabbaca doang for the people of Pasaka Village is as an embodiment of religion that contains about individual beliefs about what God has given him and intensifies social solidarity.